2020
DOI: 10.1186/s12935-020-01298-5
|View full text |Cite|
|
Sign up to set email alerts
|

Downexpression of HSD17B6 correlates with clinical prognosis and tumor immune infiltrates in hepatocellular carcinoma

Abstract: Background Hydroxysteroid 17-Beta Dehydrogenase 6 (HSD17B6), a key protein involved in synthetizing dihydrotestosterone, is abundant in the liver. Previous studies have suggested a role for dihydrotestosterone in modulating progress of various malignancies, and HSD17B6 dysfunction was associated with lung cancer and prostate cancer. However, little is known about the detailed role of HSD17B6 in hepatocellular carcinoma (HCC). Methods Clinical implication and survival data related to HSD17B6 expression in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…HS3ST1 might acts as a molecular biomarker for tumor diagnosis and prognosis ( 35 ). HSD17B6 has important functionality in androgen catabolism and was remarkably downregulated in hepatocellular carcinoma, which predicted poor prognosis and high tumor immune infiltrates ( 36 ). It was identified that LIPE is up-regulated in cervical cancer and promotes cell proliferation, invasion, and epithelial-mesenchymal transformation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…HS3ST1 might acts as a molecular biomarker for tumor diagnosis and prognosis ( 35 ). HSD17B6 has important functionality in androgen catabolism and was remarkably downregulated in hepatocellular carcinoma, which predicted poor prognosis and high tumor immune infiltrates ( 36 ). It was identified that LIPE is up-regulated in cervical cancer and promotes cell proliferation, invasion, and epithelial-mesenchymal transformation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ten genes related to REXO4 were shown in Figure 9, among them, HSD17B6, URM1, HPX, C6, ZMYND19 were playing a key part in the advancement of liver cancer (12)(13)(14)(15)(16). In an attempt to gain valuable insight regarding the biological importance of REXO4 in HCC, REXO4 co-expression mode in the LIHC cohort was examined Tumor Tissue Normal Tissue using the function module of LinkedOmics.…”
Section: Rexo4 Co-expression Genes In Hccmentioning
confidence: 99%
“…Among the DEGs from the three cohorts, three MRGs (B3GNT3, ADH1B, and HSD17B6) were overlapped (Figures 5A-C), and their expression levels were significantly correlated with MRGPI (Supplementary Figure S6). The three MRGs had been reported to be associated with other cancers (17)(18)(19), but few studies reported their role in LUAD.…”
Section: Biological Phenotypes Associated With the Mrgpimentioning
confidence: 99%
“…HSD17B6 could convert 3 alpha-adiol to dihydrotestosterone that was closely related to the development of many tumors (20). Lv et al (17) reported that low expression of HSD17B6 correlated with multiple ICGs expression in hepatocellular carcinoma. In this study, we observed that the expression level of HSD17B6 was negatively correlated with PD-1 (r = −0.20 and P < 0.001 in TCGA, r = −0.19 and P < 0.001 in GSE72094), PD-L1 (r = −0.11 and P = 0.033 in TCGA, r = −0.14 and P = 0.003 in GSE72094), and LAG3 (r = −0.22 and P < 0.001 in TCGA, r = -0.21 and P < 0.001 in GSE72094) (Figure 5H), suggesting that low HSD17B6 expression potentially played an important role in mediating immune evasion.…”
Section: Biological Phenotypes Associated With the Mrgpimentioning
confidence: 99%